Evaluation of Biomass and Chitin Production of Morchella Mushrooms Grown on Starch-Based Substrates - Aikaterini Papadaki; Panagiota Diamantopoulou; Seraphim Papanikolaou; Antonios Philippoussis (Foods, 2019)
Morchella sp. is one of the most expensive mushrooms with a high nutritional profile. In this study, the polysaccharide content of Morchella species was investigated. Specifically, mycelium growth rate, biomass production, sclerotia formation, and glucosamine and total polysaccharides content of six Morchella species grown on a starch-based media were evaluated. Submerged fermentations in potato dextrose broth resulted in a glucosamine content of around 3.0%. In solid-state fermentations (SSF), using potato dextrose agar, a high linear growth rate (20.6 mm/day) was determined. Increased glucosamine and total polysaccharides content were observed after the formation of sclerotia. Biomass and glucosamine content were correlated, and the equations were used for the indirect estimation of biomass in SSF with agro-industrial starch-based materials. Wheat grains (WG), potato peels (PP), and a mixture of 1:1 of them (WG−PP) were evaluated as substrates. Results showed that the highest growth rate of 9.05 mm/day was determined on WG and the maximum biomass yield (407 mg/g) on WG−PP. The total polysaccharide content reached up to 18.4% of dried biomass in WG−PP. The results of the present study proved encouraging for the efficient bioconversion of potato and other starch-based agro-industrial waste streams to morel biomass and sclerotia eliciting nutritional and bioactive value.